2004
DOI: 10.1111/j.1365-2044.2004.03459.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic impact of intra‐operative transoesophageal echocardiography during noncardiac surgery*

Abstract: SummaryThe impact of transoesophageal echocardiography on haemodynamic management during elective noncardiac surgery was assessed during this observational prospective database analysis. Ninety-nine consecutive patients were studied, who were at risk of intra-operative myocardial ischaemia or haemodynamic instability (Class II indications) and were undergoing vascular, visceral or chest surgery. A total of 165 new echocardiographic findings were recorded. Based on these findings changes in drug therapy were ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 36 publications
1
45
0
2
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17][18][19][20] All the studies were reported as comprehensive examinations, which was reflected in the broad diversity of diagnoses. As described previously, preoperative exams occurred immediately prior to induction of anesthesia and data from pre-assessment clinic exams were not included.…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20] All the studies were reported as comprehensive examinations, which was reflected in the broad diversity of diagnoses. As described previously, preoperative exams occurred immediately prior to induction of anesthesia and data from pre-assessment clinic exams were not included.…”
Section: Resultsmentioning
confidence: 99%
“…Influence of TEE on fluid therapy during liver transplantation is also well documented in literature, up to 50% in some series [59]. Although transgastric views are limited, the short axis view gives a better assess to the circumference of the left ventricle by overpassing posterior retraction of the stomach [60].…”
Section: Liver Transplantationmentioning
confidence: 98%
“…Assessment of preload and myocardial contractility is an essential accompaniment to the successful modern management of the highrisk surgical patient. Echocardiography can accurately predict fluid responsiveness and enable informed changes in vasoactive drugs [51,[61][62][63][64][65]. Unlike alternative flow-based monitors that display a numerical value, echocardiography can display real-time changes in valvular function or the development of ventricular wall motion abnormality.…”
Section: Intra-operative Haemodynamic Monitoringmentioning
confidence: 99%
“…Segmental wall motion abnormalities are alarmingly common, seen in 20-32% of patients undergoing surgery, and there is a clear association with coronary ischaemia and cardiac events [66]. Prompt detection and treatment can result in the resolution of myocardial ischaemia, and TOE has been demonstrated to be effective when used in this manner [51]. Transoesophageal echocardiography is twice as sensitive to left ventricular wall motion abnormalities when compared with ECG monitoring, although clinical and enzyme correlation with intra-operative findings is currently lacking [67].…”
Section: Intra-operative Haemodynamic Monitoringmentioning
confidence: 99%